Digital Identity Analysis of Tretan Muslim: a Case Study of a Content Creator's Digital Identity Formation and Management: Analisis Identitas Digital Tretan Muslim: Studi Kasus Pembentukan dan Pengelolaan Identitas Digital Seorang Kreator Konten - Alvandaru, M. Hafid; Jona, Bryan Mahendra Putra (Procedia of Social Sciences and Humanities, 2025)
This study examines how Tretan Muslim, a prominent Indonesian content creator, constructs and manages his digital identity across various social media platforms. Using qualitative analysis and digital ethnography methods, this research explores his strategies in managing context collapse, maintaining authenticity, and handling participatory surveillance risks. The findings reveal sophisticated multi-platform strategies, effective context collapse management, and balanced risk-opportunity handling in digital identity maintenance. This study contributes to understanding digital identity management in the Indonesian social media landscape, particularly among public figures navigating between entertainment and social commentary. Results indicate that successful digital identity management requires strategic platform utilization, consistent authenticity maintenance, and effective risk management approaches. Highlights: Multi-Platform Strategy – Tretan Muslim employs tailored approaches across different social media platforms to manage his digital identity effectively. Authenticity & Context Collapse – He balances authenticity while navigating diverse audience expectations and overlapping social contexts. Risk & Opportunity Management – He strategically handles participatory surveillance risks while leveraging opportunities for engagement and influence. Keywords: Digital Identity, Content Creator, Social Media, Context Collapse, Authenticity, Participatory Surveillance